2009
DOI: 10.1161/circulationaha.109.849539
|View full text |Cite
|
Sign up to set email alerts
|

Hypercoagulability Inhibits Monocyte Transendothelial Migration Through Protease-Activated Receptor-1-, Phospholipase-Cβ-, Phosphoinositide 3-Kinase-, and Nitric Oxide-Dependent Signaling in Monocytes and Promotes Plaque Stability

Abstract: Background-Clinical studies failed to provide clear evidence for a proatherogenic role of hypercoagulability. This is in contrast to the well-established detrimental role of hypercoagulability and thrombin during acute atherosclerotic complications. These seemingly opposing data suggest that hypercoagulability might exert both proatherogenic and antiatherogenic effects. We therefore investigated whether hypercoagulability mediates a beneficial effect during de novo atherogenesis. Methods and Results-De novo at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
86
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 44 publications
1
86
2
Order By: Relevance
“…Proteinuria levels remained significantly elevated in aPC-treated PAR-3 Ϫ/Ϫ mice (0.50 vs 0.29 mg/mL in aPC-treated wild-type mice, P Ͻ .005, Figure 7A) or in mice pretreated with the cell penetrating lipid-conjugated PAR-1 antagonist Ppal12S (0.68 mg/mL vs 0.29 mg/mL in aPC-treated mice, P Ͻ .005, Figure 7A). [32][33][34] Expression of nephrin was markedly reduced in LPS-treated wild-type mice, reflecting podocyte injury (1.4 AU vs 2.4 AU in PBS-treated controls, P ϭ .02, Figure 7B). 22 Nephrin expression was maintained in aPC-treated wild-type mice (2.3 AU in LPS ϩ aPC-treated mice vs 1.4 AU in LPS only mice, P ϭ .03, Figure 7B), but not in aPC-treated PAR-3 Ϫ/Ϫ mice or in mice concomitantly treated with aPC and the PAR-1 antagonist Ppal12S (1.2 AU in PAR-3 Ϫ/Ϫ and 0.9 AU in Ppal12S-treated vs 2.3 AU in aPC-treated mice, P ϭ .03 and P ϭ .01, respectively, Figure 7B).…”
Section: Apc-par-3 Signaling Is Essential In Protecting Against Podocmentioning
confidence: 98%
“…Proteinuria levels remained significantly elevated in aPC-treated PAR-3 Ϫ/Ϫ mice (0.50 vs 0.29 mg/mL in aPC-treated wild-type mice, P Ͻ .005, Figure 7A) or in mice pretreated with the cell penetrating lipid-conjugated PAR-1 antagonist Ppal12S (0.68 mg/mL vs 0.29 mg/mL in aPC-treated mice, P Ͻ .005, Figure 7A). [32][33][34] Expression of nephrin was markedly reduced in LPS-treated wild-type mice, reflecting podocyte injury (1.4 AU vs 2.4 AU in PBS-treated controls, P ϭ .02, Figure 7B). 22 Nephrin expression was maintained in aPC-treated wild-type mice (2.3 AU in LPS ϩ aPC-treated mice vs 1.4 AU in LPS only mice, P ϭ .03, Figure 7B), but not in aPC-treated PAR-3 Ϫ/Ϫ mice or in mice concomitantly treated with aPC and the PAR-1 antagonist Ppal12S (1.2 AU in PAR-3 Ϫ/Ϫ and 0.9 AU in Ppal12S-treated vs 2.3 AU in aPC-treated mice, P ϭ .03 and P ϭ .01, respectively, Figure 7B).…”
Section: Apc-par-3 Signaling Is Essential In Protecting Against Podocmentioning
confidence: 98%
“…For the myocardial IRI model (left anterior descending artery ligation for 90 minutes followed by 24 hours of reperfusion), mice were injected with phosphate-buffered saline (PBS; control; equal volume intraperitoneally [IP]), aPC (1 mg/kg IP), 24 aPC-HAPC1573 complex (aPC was preincubated before injection with HAPC1573 antibody at a 1:1 molar ratio for 10 minutes under gentle agitation to block its anticoagulant activity), [24][25][26][27] an aPC variant lacking specifically anticoagulant function (3K3A-aPC; 1 mg/kg IP), 28,29 the inhibitory PAR-1 pepducin (P1pal-12S; 2.5 mg/kg subcutaneously) followed by aPC (1 mg/kg IP), 26,30,31 or parmodulin-2 (5 mg/kg IV) 32 reperfusion), 25 mice were injected with PBS (control; 1 mg/kg IP) or aPC (1 mg/kg IP) 30 minutes before IRI. P1pal-12S and parmodulin-2 have been previously described.…”
Section: In Vivo Intervention Studiesmentioning
confidence: 99%
“…P1pal-12S and parmodulin-2 have been previously described. [30][31][32][33] Infarct size was determined as described in the supplemental Methods.…”
Section: In Vivo Intervention Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…PAR4 KO mice with an atherosclerosis-prone apolipoprotein E-deficient (ApoE−/−) background, fed a high cholesterol diet, display unaffected plaque formation and indifferent plaque surface area coverage . Interestingly, consistent with the observation that PAR1 does not mediate murine platelet response to thrombin, a recent report has indicated that it is the action of thrombin on monocytes via PAR1 that promotes plaque stability during atherogenesis in mice by inhibiting transendothelial migration to reduce macrophage accumulation (Seehaus et al, 2009). Further, use of PAR1 KO mice demonstrated a potential role for PAR1 in regulation of murine vasculature independent of platelet activation in response to injury, likely mediated by tissue remodeling and extracellular matrix synthesis .…”
Section: Par2 Allergic Airway Inflammationsupporting
confidence: 54%